Differences between epilepsy patients under politherapy and epilepsy patients under monotherapy [Politerapi kullanan epilepsi hastalarının monoterapi kullanan hastalardan farklılıkları] - (:unkn) unknown (Marmara University, 2012)
Objective: This study aimed to evaluate demographical variables, clinical features, neurological examination and cranial imaging results which cause or determine the necessity for politherapy treatment in epilepsy patients. Patients and Methods: The patient files of 785 epileptic patients were followed by Marmara University Epilepsy Outpatient Clinic were scanned retrospectively and a questionnaire was filled in for each file. Patients were grouped as monotherapy or politherapy, considering the number of antiepileptics they used. The demographical variables, clinical features, neurological examination and imaging results of the two groups were compared. The results were analyzed by Student's-t test and chi-square tests. Results: A history of craniotomy and intracranial tumors is more frequent in politherapy patients. Also, simple partial seizure, convulsive status epilepticus, pathological neurological examination findings, abnormal EEG, cranial imaging (MRI/CT) and SPECT results were found to be higher in politherapy patients. Conclusion: Politherapy is an important step in epilepsy treatment. However, because of drug-drug interactions and drug side effects it is not the first choice. Determining the differences between patients who use politherapy and monotherapy will help recognizing the clinical data which may lead to politherapy need. © Marmara Medical Journal, Published by Galenos Publishing.
Keywords: Epilepsy; Etiology; Politherapy